Sustainable Development : Challenges and Strategies in South Asia, Spotlighting Pakistani Higher Education - Sain, Zohaib Hassan; Nurtina, Sitti; Agoi, Moses Adeolu; Thelma, Chanda Chansa (Journal of Information Systems and Technology Research, 2024)
An analysis of the Sustainable Development Goals (SDGs) in South Asian countries, including Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka, highlights the presence of socio-economic and political obstacles. This research examines the challenges that are impeding the accomplishment of Sustainable Development Goals (SDGs), such as poverty (SDG 1), health (SDG 3), education (SDG 4), and economic growth (SDG 8), utilizing data from the World Bank, IMF, WHO, and FAO. The financial facts given highlight the immediate need for significant actions. The report recommends that Developed Countries (DCs) take on a crucial role by allocating at least one per cent of their Gross National Product (GNP) towards development aid. Achieving success in implementing the Sustainable Development Goals (SDGs) requires effective governance and the execution of structural changes. The report advocates for providing development aid from developed countries to underdeveloped countries (UDCs), aiming to foster the exchange of experiences to address common difficulties. The conclusions guide South Asian governments in formulating efficacious economic strategies to achieve the Sustainable Development Goals by 2030. In addition, the study examines 26 papers issued by the Higher Education Commission (HEC) that investigate sustainability in Pakistani Higher Education Institutions. An analysis of this research reveals both advancements and obstacles in pursuing Education for Sustainable Development (ESD). Various stakeholders actively participate in the transformational process, including administrators, leaders, instructors, and students. The examination focuses on governance, communication, coordination, and campus outreach and tackles problems. Aligning with the Sustainable Development Goals (SDGs), prioritizing logistical assistance and excellent education (SDG 4) is crucial. The study is a manual for educators, policymakers, and curriculum creators to promote Sustainable Development, assisting researchers in formulating inquiries for sustainable development objectives.